Emergency care of LGBTQIA+ patients requires more than understanding the acronym. Issue 1 (23rd June 2022) - Hsiang, Elaine; Ritchie, Amanda M.; Lall, Michelle D.; Driver, Lachlan; Moll, Joel; Sonn, Brandon; Totten, Vicken Y.; Williams, Dustin B.; McGregor, Alyson J.; Egan, Daniel J.
Abstract: Emergency physicians (EPs) frequently deliver care to members of the LGBTQIA+ community in the emergency department. This community suffers from many health disparities important to understand as part of comprehensive care, and these disparities are infrequently discussed in emergency medicine education. Previous data also suggest a need for broader education to increase the comfort of EPs caring for LGBTQIA+ patients. A group of content experts identified key disparities, opportunities for expanded education, and strategies for more inclusive care of LGBTQIA+ patients.